Studi Kelayakan Dan Perancangan Serta Implementasi Turbin Pada Proyek PLTMH Di Kabupaten Sleman Yogyakarta - Tarmizi, Achmad; Wardono, Herry (Fakultas Teknik Universitas Lampung, 2020)
The Regional Government of Sleman Regency will build a PLTMH by utilizing the potential of hydropower in Girikerto village, which is one of the renewable energy sources. This research is based on the results of a feasibility study conducted by the author by conducting a field study to retrieve location data by paying attention to technical, economic and social, then a literature study and data analysis are carried out to determine the type of turbine and the most appropriate characteristics for the PLTMH at that location. From the results of the data analysis and by conducting careful calculations and taking into account the conditions of the PLTMH project location, the most appropriate turbine to be used is the turbine Cross Flow type. Besides having a simple construction, this turbine can also be designed for a large enough capacity and is easier to fabricate. Another result obtained is the value of the ratio of benefits to costs of 0.79 (less than 1). This means that the construction of this PLTMH is considered uneconomic, but with the power it can generate at 10.58 kW, it will certainly be able to illuminate and supply electricity (a huge benefit) for dozens of Girikerto villagers.